The Effect of the Drills-Based Learning Model on the Improvement of Futsal Dribbling Skills in Indoviska Futsal Academy Players - Rewa Ridozuta; Asep Sujana Wahyuri; Umar Umar; Aldo Naza Putra (STKIP Singkawang, 2025)
This study aims to analyze the influence of drills-based learning model on futsal dribbling skills in Indoviska Futsal Academy players of Indragiri Hilir Regency, as well as to test the interaction between training methods and player agility levels. The method used was an experiment with a two-track ANOVA design, with a sample of players divided by type of exercise and agility level (high and low). The results showed that the Drill-based learning model improved dribbling skills, with an average score of 15.58 compared to 17.38. In addition, there was an interaction between training methods and agility levels, where players with high and low agility showed better results with Shuttle Run training than Corner Drill. In conclusion, the drills-based learning model is influential in improving dribbling skills compared to Corner Drill, so it can be used as an alternative in futsal training programs.